Implementasi dan Relevansi Kebijakan Dalam Pemerataan Pendidikan: Studi Literatur Pelayanan Publik - Kasypul Anwar (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Every development of a country inevitably goes through a series of policies that must be implemented, including in the field of education. This study aims to collect evidence from scientific studies on the suitability of educational policy formulation with actual implementation. A series of related literature searches across various journals, publications, books and websites actively addresses educational policy and practice issues to support this research. We can use this data as study data after going through a series of studies related to the critical assessment data coding system and conclude after an in-depth interpretation of the data using a phenomenological approach. The data is completely valid and up-to-date. Based on the results of the research and discussion of this research, it can be concluded that the implementation of education policy is an action that is closely related to the way education is carried out with full responsibility, accountability in accordance with its duties. programmed by the constitution to improve the quality and accountability of education. The results of this study are expected to be an important input for efforts to develop similar research in future research activities.